Essential Thrombocythemia Following Immune Thrombocytopenia With JAK2 V617F Mutation: A Case Report - Mehrdad Payandeh; Mehrnoush Aeinfar; Kimiya Dadashizadeh; saba yari (Case Reports in Clinical Practice, 2021)
Immune Thrombocytopenia (ITP) is an autoimmune bleeding disorder. Tyrosine Kinase JAK2 (JAK2 V617F) mutation occurs in nearly 60% of Essential Thrombocythemia (ET) patients. Both diseases produce impaired platelet. We describe a case with ET following ITP. So far, only 3 reports described ET following ITP. We report the fourth patient with JAK2 V617F mutation at the onset of ITP presented 20 years ago that needed splenectomy. The association of these two diseases may recommend similar pathogenic mechanisms between Myeloproliferative Neoplasms (MPNs) and ITP that should be further explored.